Subcutaneous administration of benzathine benzylpenicillin G has favourable pharmacokinetic characteristics for the prevention of rheumatic heart disease compared with intramuscular injection: a randomized, crossover, population pharmacokinetic study in healthy adult volunteers. (22nd July 2020) - Kado, Joseph H; Salman, Sam; Henderson, Robert; Hand, Robert; Wyber, Rosemary; Page-Sharp, Madhu; Batty, Kevin; Carapetis, Jonathan; Manning, Laurens
Abstract: Background: Benzathine penicillin G has been used as monthly deep intramuscular (IM) injections since the 1950s for secondary prevention of acute rheumatic fever and rheumatic heart disease (RHD). Injection frequency and pain are major programmatic barriers for adherence, prompting calls for development of better long-acting penicillin preparations to prevent RHD. We hypothesized that subcutaneous (SC) administration of benzathine penicillin G could delay penicillin absorption when compared with IM injections. Methods: To compare the pharmacokinetic profile and tolerability of benzathine penicillin G according to different routes of administration, 15 healthy males participated in a randomized crossover study to receive benzathine penicillin G by either SC or IM routes, with a 10 week washout period before the second dose by the alternative route. Ultrasound guidance confirmed injection location. Penicillin concentrations and pain scores were measured for 6 weeks following injections. Results: SC administration was well tolerated with no significant differences in pain scores. Following SC injection, the principal absorption half-life (95% CI) was 20.1 (16.3–29.5) days and 89.6% (87.1%–92.0%) of the drug was directed via this pathway compared with 10.2 (8.6–12.5) days and 71.3% (64.9%–77.4%) following IM administration. Lower peak and higher trough penicillin concentrations resulted following SC injection. Simulations demonstrated that SC infusion of higher doses of benzathine penicillin G could provide therapeutic penicillin concentrations for 3 months. Conclusions: SC administration of benzathine penicillin G is safe and significantly delays penicillin absorption. High-dose benzathine penicillin G via the SC route would fulfil many product characteristics required for the next generation of longer-acting penicillins for use in RHD.